Turner’s 1836 Alpine Crossing and the Little Ice Age Portrayed in Val Veny and Val Ferret; a Geography of the Sublime - Martin P. Kirkbride; Susan P. Mains; Vanessa Brazier (Revue de Géographie Alpine)
The English artist J.M.W. Turner made his second visit to upper Val d’Aosta in 1836, after which he produced several significant paintings. Here, we accurately locate two of these works and relate them to the climatic and geomorphological environment of the time. We combine critical geomorphological and cultural geographic analyses to derive a more holistic appraisal of Turner’s artistic motivations and methods in his Alpine works. The first is a watercolour of Mont Rouge de Peuterey from across the Glacier du Miage. The second is a major oil painting re-imagining of the 1717 Triolet disaster which conflates the complex geomorphological processes of this rock-ice avalanche and subsequent outburst flood into a single dramatic scene. Turner’s visit coincided with the mid-nineteenth century maximum advance of glaciers in the region allowing him to witness dynamic geomorphological processes in close proximity. The precise viewpoints of these scenes demonstrate that Turner spent some time in the area to seek out preferred locations and that he was aware of considerable details of local history. The paintings speak of an immersion in the environment of the time, and their study yields fruitful insights into the complex relationships between geography and landscape art.